Cooperation and bacterial pathogenicity: an approach to social evolution - Alfonso Molina,C (Sociedad de Biología de Chile, 2014)
Kin selection could provide an explanation for social behavior in bacteria. The production of public goods such as extracellular molecules is metabolically costly for bacteria but could help them to exploit nutrients or invade a host. Some bacterial cells called social cheaters do not produce public goods; however, they take advantage of these extracellular molecules. In this review, the relationships between social behavior, cooperation, and evolution of bacterial pathogenicity are analyzed. This paper also examines the role of horizontal transfer of genes encoding for virulence factors and how the movement of mobile genetic elements would influence the pathogenicity and social relationships. Moreover, the link between ecological relationships and evolution in entomopathogenic bacteria, focusing on Bacillus thuringiensis is considered. Finally, the findings obtained with B. thuringiensis are extrapolated on Bacillus pumilus 15.1, an entomopathogenic strain whose pathogenicity is not understood yet.